Caracterização do Sedimentos de Fundo e Dinâmica Sedimentar da Enseada de Jurujuba (Baía de Guanabara), Niterói, RJ. - BAPTISTA NETO, JOSÉ ANTONIO; DA SILVA, MARIA AUGUSTA MARTINS (Pesquisas em Geociências, 1996)
Sixty-four bottom surface sediment samples were collected in Jurujuba Bight using a Dietz LaFond grab sampler. They were analysed for grain size distribution, shape, mineralogy and geochemistry. From the association between the Bight bottom morphology and sediment characteristics, it was possible to establish the sedimentary dynamics. This allowed a division of the Bight into three sedimentary zones: an outer, sand-dominated zone of relatively high wave and current energy, an inner zone characterized by very calm conditions and clay/mud deposition and an intermediary zone of mixed sedimentary characteristics.